Reading, Encoding, Annotating, and Pondering Technique As Learning Process In Pandemic Era to Improve Reading Comprehension Stability or Students - Susanto, Ferri (CV. Inara, 2021)
The students' reading comprehension is very lowat the pandemic era, Theyare difficult to understand the text, they don’t haveEnough English vocabulary, Many teachers/lecturer used techniques that wereless precise in teaching reading, and the students got reading comprehension scores below the minimum completion criteria (KKM). This research aims to determine whether using Reading, Encoding, Annotating, and Pondering techhnique as Learning process in pandemic era to improve reading comprehension stability for students.This research is conducted by using descriptive qualitative method, which describe of students’s problem at pandemic era by zoom in the Internet after that, analyze the data which used percentage.The researcher also has done pre-assesment for supporting accurate data.The subjects of this research were 20 students, consisted 11 females and 9 males. The subject Instrument used in this research is reading comprehension test, researcher observation cheklits and field notes, student observation Cheklist and field notes, interview and documentation by zoom at the Internet. According to avarage results, the increasing for students' reading comprehension ability on the pre-assessment is the average student reaches, (55.14%), learning 1 (62.15%), learning 2 (70.14%), and learning 3 (75.65%) avarage students’ score increase and got standardization of school. Based on the result in each levels which there is indeed REAP technique could increasing students’ reading comprehension text.